Business Retention and Expansion (BRE) Programs: Responding to Business Concerns - Henry M. Cothran (EDIS)
FE656, a 3-page fact sheet by Henry M. Cothran, is ninth in a series on establishing Business Retention and Expansion (BRE) programs. It outlines a procedure for identifying and tracking issues identified during a business survey. Includes references. Published by the UF Department of Food and Resource Economics, April 2008.